Risk of contamination of semen, vaginal secretions, follicular fluid and ovarian medulla with SARS-CoV-2 in patients undergoing ART. Issue 2 (6th November 2021) - Kteily, K; Pening, D; Diaz Vidal, P; Devos, M; Dechene, J; Op de Beeck, A; Botteaux, A; Janssens, S; Van den Abbeel, E; Goldrat, O; Delbaere, A; Demeestere, I
Abstract: STUDY QUESTION: Can severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mRNA be detected in the reproductive tract of asymptomatic patients undergoing ART? SUMMARY ANSWER: SARS-CoV-2 mRNA is not detectable in semen, follicular fluid, vaginal secretions or residual medulla from ovarian tissue cryopreservation procedures in asymptomatic patients who undergo ART, irrespective of the results of a triage questionnaire and a nasopharyngeal SARS-CoV-2 RNA detection test. WHAT IS KNOWN ALREADY: The SARS-CoV-2 pandemic had a huge impact on the activities of fertility clinics. Although some studies reported the presence of SARS-CoV-2 mRNA in the reproductive system during or after acute COVID-19 symptomatic infections, uncertainties remain regarding the presence of viral mRNA in the reproductive material and follicular fluid of asymptomatic patients undergoing ART. STUDY DESIGN, SIZE, DURATION: An observational cohort trial of residual material samples including semen, follicular fluid, vaginal secretions and ovarian medulla was conducted during the second pandemic wave in Brussels from September 2020 to April 2021. PARTICIPANTS/MATERIALS, SETTING, METHODS: All patients who underwent ART (IUI, IVF/ICSI, oocyte and ovarian tissue cryopreservation) responded to a triage questionnaire at the beginning and end of the cycle and underwent nasopharyngeal swab collection for SARS-CoV-2 RNA detection by RT-PCR before the procedure according to standard recommendations. For semen analysis, only the questionnaire was requested the day before the sample collection. The ART cycles of patients with positive nasopharyngeal SARS-CoV-2 RNA detection tests and/or questionnaires were cancelled except for those that could not be postponed. After providing informed consent, swabs on residual materials were collected the day of the oocyte, ovarian tissue or semen collection and were processed for RT-qPCR. MAIN RESULTS AND THE ROLE OF CHANCE: A total of 394 samples from 291 patients were analysed. Amongst them, 20 samples were obtained from patients with a positive questionnaire but negative nasopharyngeal SARS-CoV-2 test and 20 others were from patients with a positive nasopharyngeal SARS-CoV-2 test. The remaining samples were collected from patients with a negative or unknown nasopharyngeal SARS-CoV-2 test and/or a negative or unknown triage questionnaire. Viral RNA for SARS-CoV-2 was undetectable in all of the samples. LIMITATIONS, REASONS FOR CAUTION: Considering the cancellation policy, only a limited number of samples from patients with positive triage questionnaires or nasopharyngeal SARS-CoV-2 tests were included in the analysis. WIDER IMPLICATIONS OF THE FINDINGS: The study suggested that there was no risk of reproductive tract contamination by SARS-CoV-2 in asymptomatic patients, irrespective of the results from a triage questionnaire or nasopharyngeal SARS-CoV-2 test. The results suggested that no additional measures to prevent staff or cross-patient contamination need to be implemented in the IVF and andrology laboratories. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by the Université Libre de Bruxelles and by a grant from Ferring. A.D. and I.D. received a grant from Ferring for the study. The authors have no other conflict of interest to declare related to this study. TRIAL REGISTRATION NUMBER: N/A.